Modification of The Bacterial Abundance Properties of Water by Immersed Non-Activated Charcoal - Aurelie, Dzenga Njeunkam; Luciane Marlyse, Moungang; Samuel, Eheth Jean; Ache Roland, Ndifor; Moïse, Nola (Clinical Medicine And Health Research Journal, 2024)
The present studies aim at reducing the planktonic bacterial load in drinking water using non-activated charcoal. The evaluation is dependent on the incubation time and the different physiological states of the bacterial cells. Three bacteria (Vibrio cholerae, Escherichia coli and Staphylococcus aureus) and two charcoal substrates (Okan and Tali) were used for the experimentation. The Bacteria adhered to charcoal fragments in varying degrees. Overall, the concentrations of fixed Vibrio cholerae reached 53.4x107 CFU/cm2 and 39.6x107 CFU/cm2 after 9 hours of contact in exponential phase on the Okan and Tali respectively. Those of fixed Staphylococcus aureus reached 5.8x106 CFU/cm2 after 3 hours of contact in exponential phase and 3.4x106 CFU/cm2 after 3 and 6 hours of contact in the same phase, on the Okan and the Tali, respectively. The highest abundances of Escherichia coli adhered to the charcoal fragments were 50.4x107 CFU/cm² on Okan and 53.2x107 CFU/cm² on Tali after 9 hours of contact in the exponential phase. The highest adsorption coefficient (639.06 adhered cells/cm2) was noted on Okan in the exponential phase with Vibrio cholerae cells; and the lowest (1.02 adhered cells/cm2) on Tali in stationary phase with Staphylococcus aureus. The incubation time significantly (P<0.01) influenced the adhesion of bacterial cells to charcoal substrates. Although the adsorption capacity and intensity of Okan were relatively higher, the comparison of the adsorption potential of the two substrates considered did not reveal any significant difference (P>0.05), reflecting the absence of the influence of the physical properties of these substrates on cell retention.